Features of the application of administrative legal acts in the practice of the Republic of Azerbaijan, the Kyrgyz Republic and the Republic of Tajikistan - Shahriyar, Jafarzada (Теоретичні питання юриспруденції і проблеми правозастосування: виклики ХХІ століття : тези доп. учасників X Міжнар. наук.-практ. конф. (Харків, 25 трав. 2025 р.), 2025)
One of the most difficult theoretical and practical problems, both in legal science in general and in administrative law, is the problem of administrative acts. Traditionally, more attention is paid to the study of legislative acts in force. It should be stated that when adopting administrative acts, the legislative acts in force are taken as a guide. The article presents a general description of the Law of the Republic of Azerbaijan On Administrative Proceedings, the Administrative Procedure Code of the Republic of Azerbaijan, the Law of the Kyrgyz Republic On the Fundamentals of Administrative Activity and Administrative Procedures, the Administrative Procedure Code of the Kyrgyz Republic and the Code of Administrative Procedures of the Republic of Tajikistan. The content of the main concepts is disclosed.